From White Supremacy to White Power: the FBI, COINTELPRO-WHITEHATE, and the Nazification of the Ku Klux Klan in the 1970s - Drabble, John (American Studies, 2007)
In the 1960s, the leader of the largest Ku Klux Klan organization in the United States presumed that the Federal Bureau of Investigation was a meritorious ally engaged in a common battle against Communist subversion. During the 1970s however, Klan organizers transformed a reactionary counter-movement that had failed to preserve white supremacy by terrorizing civil rights organizers and black citizens, into a revolutionary White Power movement that engaged in terrorism against Jews and the Federal Government. Based on a forthcoming article in American Studies, this paper describes how these organizers combined latent revolutionary impulses within Klan ideology with esoteric anti-Semitic and anti-Republican discourses, infusing Christian Americanism-the Klan’s particular admixture of white supremacy, anticommunism, nativism, and segregationist theology -with transnational discourses of National Socialist politics, Christian Identity theology, and racial anti-Semitism. This change occurred as American race relations went through a profound transformation. The rise of neoconservatism, which attacked liberalism and the welfare state while eschewing overtly racial rhetoric, was particularly important in this context, as Americans learned to understand race in “nonsystematic, nonstructural terms.” Like neoconservatives, Klansmen also shifted focus from racial minorities to the Federal Government, but they clung to biological notions of race. As their former segregationist allies discarded the formal institutions of white supremacy, Klansmen came to realize that it was no longer possible to revive white supremacy or to attract a mass base. They turned to esoteric conspiratorial discourses to cope with this predicament. This development occurred within larger processes of political, social, and cultural restructuring during the most recent wave of globalization. Yet this particular trajectory, from a localized white supremacist vigilantism inspired by white supremacist nationalism, to a transnational cultic milieu of revolutionary terrorists inspired by White Power millennialism, was in no small part due to a successful FBI covert action program called COINTELPRO-WHITE HATE, which exposed, disrupted and helped to vitiate Klan organizations between 1964 and 1971, spurring Klan organizers to fundamentally rethink their rhetorical and organizational strategies.